Ophthalmology Practice during Peak of Coronavirus Disease 2019 (COVID-19) Pandemic: A Global Community Perspective - Zahour, John; Karadaghy, Amin; Rodrigues, Eduardo B.; Cruz, Oscar A. (Journal of Academic Ophthalmology, 2020)
Objective The rise of coronavirus disease 2019 (COVID-19) from Wuhan, China, in December 2019 has spread to more than 188 countries and has affected more than 13 million people. In response to this crisis, recommendations by the World Health Organization have changed the practice of current medicine, but there is little research as to how high-volume ambulatory specialties such as ophthalmology are adapting. The purpose of this study is to determine how ophthalmology practices are reacting and changing during the COVID-19 pandemic.Methods Approval was obtained from Saint Louis University School of Medicine Institutional Review Board. An anonymous survey was made on Google Forms and distributed to ophthalmologists throughout the world. Questions were divided into five sections: demographics, general questions, inpatient care/consults, practice management, and personal impact. The survey was opened on March 31, 2020, and closed on April 12, 2020. Statistical analysis was performed using Microsoft Excel.Results A total of 494 responders from 42 countries completed the survey. Respondents were predominantly practicing ophthalmologists (85%), with the next highest demographic being ophthalmology trainees (8%). Fear of spreading COVID-19 to patients or loved ones was the highest source of anxiety among practitioners across all practice settings and continental location (p = 0.003). The second source of anxiety varied, with private practitioners identifying financial difficulty compared with employed clinicians listing self-contamination. Anxiety levels were the same throughout all practice settings, ages, and subspecialties (p = 0.2527). Ophthalmologists listed ophthalmological Web sites/societies, discussion with colleagues, and social media as primary sources of guidance with no difference based on practice setting (p = 0.143). Finally, all continents increased their application of telemedicine as a patient care modality, with North America expanding significantly more than other continents.Conclusion The COVID-19 pandemic has drastically changed ophthalmology practice and has added a high level of stress to ophthalmologists globally. These results demonstrate that clinicians are largely alike across age group, country, and specialty, but key differences in source of anxiety and in application of telemedicine highlight diversity in culture and reaction to the pandemic.
Keywords: survey; COVID; coronavirus; guidelines; telemedicine